Formula allocation: the regional allocation of budgetary funds for measures of active labour market policy in Germany - Uwe Blien; Franziska Hirschenauer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
A common problem of regional policy is the distribution of funds to regional units. To follow the specific purpose of this budgeting process in a rational way this is often done in a formula allocation on the basis of official statistics. In the paper this is shown with the example of funds for active labour market policy. In Germany, measures of active labour market policy - e.g. training measures, integration subsidies and job creation schemes - are paid from a common budget. For the allocation of these budgetary funds (amounting to EURO 0,194 billion in 2004) to the regions of the Federal Republic of Germany, a formula was developed which was to be based essentially on a labour market indicator. The criteria for the development of a formula allocation were: most accurate fit to the legal guidelines of the Social Code, transparency of the procedure, openness for necessary policy decisions, scientific correctness in implementation, efficiency of the whole process. Here the procedure used in constructing the distribution process is explained and the distribution result is set out. Both were finally passed by the Supervisory Board of the Federal Employment Agency in Germany.
Keywords: H11; J00; R10; 330; Arbeitsmarktpolitik - Finanzierung; regionale Verteilung; Budget; Indikatorenbildung